(untitled) (Research, Society and Development, 2024)
Feline hyperesthesia, often referred to as waving skin syndrome or nervous cat disease, is a rare and still poorly understood condition that affects cats. The main symptoms include hypersensitivity, muscle spasms, excessive licking, and other abnormal behaviors. Diagnosis is challenging and usually involves a combination of clinical history, physical examinations, and exclusion of other conditions that may present similar symptoms. Thus, this report aims to describe a case of feline hyperesthesia treated in Cacoal-RO, where the diagnosis was made through the analysis of clinical signs, laboratory test results, and anamnesis. The therapeutic management involved the use of dipyrone, tramadol, midazolam, and dexamethasone, highlighting the importance of a multimodal approach for controlling pain, inflammation, and anxiety, with the aim of improving the animal’s quality of life.